Probing substituent effects in phosphinoamine ligands using Mo(CO)5L complexes. (17th February 2015) - Lee, Kyle H.; Napoline, J.W.; Bezpalko, Mark W.; Foxman, Bruce M.; Thomas, Christine M.
Graphical abstract: A series of Mo(CO)5 L complexes have been synthesized, where L = a series of phosphinoamine ligands, R2 PNHR′. The effects of variations in phosphorus and nitrogen substituents on phosphine donor properties have been established using infrared CO stretches as a spectroscopic probe. Abstract: Recent work has revealed substantial differences in the structure, spectroscopic properties, and reactivity of heterobimetallic Zr/Co complexes of the general form XZr(R′NPR2 )3 CoY (R′ =  i Pr, 2, 4, 6-trimethylphenyl, 3, 5-dimethylphenyl; R = Ph, i Pr; X, Y = halides or neutral donor ligands) as a function of nitrogen and phosphorus donor atom substituents. To probe the electronic differences between these ligands, a series of Mo(CO)5 (R2 PNHR′) complexes has been synthesized (R = Ph, R′ =  i Pr (2a ); R =  i Pr, R′ =  i Pr (2b ), 2, 4, 6-trimethylphenyl (2c ), 3, 5-dimethylphenyl (2d ), 4-methylphenyl (2e ), 4-trifluoromethylphenyl (2f ), 4-methoxyphenyl (2g )). Thermolysis of Mo(CO)6 with the corresponding phosphinoamine ligands1a –1g affords2a –2g . The infrared carbonyl stretching frequencies of these complexes have been compared to probe the effects of phosphorus and nitrogen substituents on the electronic properties of the phosphinoamine ligands.